Implantação de uma gestão enérgetica no setor têxtil: estudo de caso em uma indústria no Ceará - Silva, Fabrício Bandeira da (2010)
This work presents the implementation of an energy management plan, including all electrical energy use, from the supply contract with the utility to its end use, with the focus being the textile industry in the state of Ceará, which has experienced considerable growth in recent years, along with energy consumption. With the growth in the textile sector, the ratio between energy consumed and the final product should be the best possible, aimed at a reduction in production costs, showing the need for an energy management plan, which would bring about rational and efficient energy use. This plan, implemented as part of this study, used the following methodological procedures: energy diagnosis, analysis of potential savings and implementation of an energy plan in a textile factory. The MTR (Monitoring, Targeting and Reporting) technique was used, which uses information on production and consumption of energy which, after processing, provide tools to support the direction of energy management plan. It was necessary to install meters in order to execute the monitoring and tracking of energy consumption by machine, and thus a gradual reduction in the specific consumption of these machines was observed, resulting in overall energy savings.